Profeel—An open source dosimetry data visualization and analysis software. (November 2021) - Pakarinen, Tomppa; Ojala, Jarkko
Highlights: Import of measured and simulated dosimetry data to a single open-source environment Simultaneous data visualization from multiple sources Automatic percentage depth dose and beam profile quality parameter determination Gamma index, distance to agreement and dose difference analysis Additional tools for filtering, scaling Abstract: Background and objectives: This article presents Profeel, a Matlab (MathWorks Inc., MA) based open source dosimetry data visualization and analysis software. Profeel aims to support quality assurance, dosimetry and research in the field of radiotherapy by providing an environment to visualize, process and analyse measured and simulated dosimetry data from several data sources used in radiotherapy practice and research. Methods: The processing and analysis tools are based on routinely used dosimetry analysis methods, such as gamma analysis, different data normalizations and data filtering. Additionally the Profeel performs an automatic 1 dimensional profile and percentage depth dose analysis in accordance with International Electrotechnical Commission definitions. All data can be operated by user created custom functions and lower dimensionality data can be extracted from volume doses and dose planes. Results: Profeel supports data import in all 3 dimensions and offers an intuitive user interface to perform data visualization, processing and analysis between simulated and measured data. Profeel and its source code are distributed free of charge under the General Public Licence (GPL). Conclusions: Profeel has shown to be an agile tool for fulfilling various needs of several researchers and since Profeel is under constant development and is an open source project, community needs, issues and bug reports are taken into account in the development.